Legal regulation of ten-year guarantee: Comparative analytical study - امىدرس امدکخِر ڕێةاز ئٍردەاڵن ەبكر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Life depends, very simply, on housing and working, so, there must be a scale that can measure both. Human nature, in the present day, changed its pattern of behavior and its needs, and it has merged with construction and become part of it. Since settlement is linked with security, it is necessary to ensure the safety of individuals in all kinds of facilities, hence came out the insurance of buildings and constructions that is known as decimal liability insurance. Due to the importance of the decimal liability system, this article is written to evaluate its rules according to Iraqi legislations, as compared to the others, specially the French and Egyptian, to evaluate its merits and demerits from the dimensions of business and the individuals and also the required conditions to make it legal. The article also discusses the nature of the decimal liability insurance and the rights of the people who will benefit from it when it is legislated, in order to see if it is liable for the purpose for which it is legislated or not. This article discusses the foregoing subjects in two sections. This is followed by the conclusion and recommendations that improve it and make it more active